2009
DOI: 10.1021/jp9037683
|View full text |Cite
|
Sign up to set email alerts
|

CO Oxidation Catalyzed by Au−Ag Bimetallic Nanoparticles Supported in Mesoporous Silica

Abstract: We report a novel Au-Ag bimetallic nanocatalyst supported on an acidic mesoporous aluminosilicate Au-Ag@APTS-MCM prepared by a two-step synthesis procedure, which is very active for low-temperature CO oxidation. Its catalytic activity is still quite appreciable after 1 year of storage under room conditions. The silane APTS [H 2 N(CH 2 ) 3 -Si(OMe) 3 ] was used to surface functionalize mesoporous silica. The functionalized mesoporous silica was used to absorb the gold precursor AuCl 4and silver precursor AgNO 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
127
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 161 publications
(136 citation statements)
references
References 60 publications
7
127
0
2
Order By: Relevance
“…2c) [28]. Evidently, for this one-pot method, the presence of Ag induced significant sintering of particles due to the formation of AgBr, which is quite different from the two-step method we developed later [31,32].…”
Section: One-pot Methodsmentioning
confidence: 90%
See 3 more Smart Citations
“…2c) [28]. Evidently, for this one-pot method, the presence of Ag induced significant sintering of particles due to the formation of AgBr, which is quite different from the two-step method we developed later [31,32].…”
Section: One-pot Methodsmentioning
confidence: 90%
“…Nevertheless, if the two types of interactions can be manipulated well, e.g., by functionalizing the support surface to strengthen the metal-support interaction and choosing an appropriate reducing agent for rapid nucleation of the two metal species, uniform composition and size distribution might also be obtained in a well-controlled manner. In order to overcome the shortcomings of the first protocol (significant sintering by the activation process), we have developed a two-step method for the synthesis of gold bimetallic catalysts that proved effective in producing small, uniform, and sintering-resistant gold bimetallic nanoparticles on nonreducing supports such as silica and alumina [21,31,32]. A typical procedure for synthesis of silica-supported Au-Ag bimetallic catalyst using this two-step method is illustrated in Fig.…”
Section: Two-step Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Crooks and co-workers synthesized PdAu/TiO 2 using dendrimer-encapsulated alloy nanoparticles as the precursor, and found that the activities of the catalysts in CO oxidation followed the sequence PdAu/TiO 2 > Pd/TiO 2 > Au/TiO 2 [235]. Mou and coworkers synthesized AuAg/Al-MCM-41 catalysts via both a one-step approach [236][237][238][239] and a two step method [55], and demonstrated enhanced catalytic activity in CO oxidation associated with the alloyed silver. Zhang and co-workers used a similar two-step approach to prepare AuAg/SiO 2 [53], AuAg/Al 2 O 3 [53], AuCu/SBA-15 [240], and AuCu/silica gel [63] catalysts, and demonstrated their good performance in CO oxidation.…”
Section: In Situ Transformation Of Niau/sio2 Into Au-niomentioning
confidence: 99%